The New Testament speaks ; v. 1 explaining the New Testament as it was understood by its first readers - Fleming, Don C. (Manilla, Philippines. Living Books for All, 1974)
Contents : v. 1 : The four Gospels
Brethren writer.
Keywords: Bible. N.T. Gospels -- commentaries